Language Teachers’ Autonomy in EFL Classroom: A Narrative Inquiry - Gyawali, Shiva Kumar (Vox Batauli, 2023)
The study aims to find out practices undertaken by English language teachers for their autonomous development in EFL classrooms. Autonomy has become one of the most problematic and significant issues to be discussed in the field of teacher education in the recent era. This paper deals with the ways to support teachers in their classroom practices, as well as a way of improving professional practices and career development. It is based on qualitative research in general and narrative inquiry in particular. The information is based on four teachers from the community as well as institutional schools. It mainly discusses the perceptions and practices of teachers towards teacher autonomy. From the obtained information, the study found positive feelings of teachers towards employing initiatives taken regarding autonomy, and they note that other stakeholders must encourage the teachers’ efforts for successful implementation. It reveals that most schools have strong and self-empowered human resources but proper encouragement and application parts seem to be weak.